Activation of RARα Receptor Attenuates Neuroinflammation After SAH via Promoting M1-to-M2 Phenotypic Polarization of Microglia and Regulating Mafb/Msr1/PI3K-Akt/NF-κB Pathway - Tian, Yang; Liu, Binbing; Li, Yuchen; Zhang, Yongzhi; Shao, Jiang; Wu, Pei; Xu, Chao; Chen, Guangduo; Shi, Huaizhang (Frontiers in Immunology, 2022)
Background and Purpose: Subarachnoid hemorrhage (SAH) is a life-threatening subtype of stroke with high rates of mortality. In the early stages of SAH, neuroinflammation is one of the important mechanisms leading to brain injury after SAH. In various central nervous system diseases, activation of RARα receptor has been proven to demonstrate neuroprotective effects. This study aimed to investigate the anti-inflammatory effects of RARα receptor activation after SAH. Methods: Internal carotid artery puncture method used to establishe SAH model in Sprague-Dawley rats. The RARα specific agonist Am80 was injected intraperitoneally 1 hour after SAH. AGN196996 (specific RARα inhibitor), Msr1 siRNA and LY294002 (PI3K-Akt inhibitor) were administered via the lateral ventricle before SAH. Evaluation SAH grade, neurological function score, blood-brain barrier permeability. BV2 cells and SH-SY5Y cells were co-cultured and stimulated by oxyhemoglobin to establish an in vitro model of SAH. RT-PCR, Western blotting, and immunofluorescence staining were used to investigate pathway-related proteins, microglia activation and inflammatory response. Results: The expression of RARα, Mafb, and Msr1 increased in rat brain tissue after SAH. Activation of the RARα receptor with Am80 improved neurological deficits and attenuated brain edema, blood brain barrier permeability. Am80 increased the expression of Mafb and Msr1, and reduced neuroinflammation by enhancing the phosphorylation of Akt and by inhibiting the phosphorylation of NF-κB. AGN196996, Msr1 siRNA, and LY294002 reversed the therapeutic effects of Am80 by reducing the expression of Msr1 and the phosphorylation of Akt. In vitro model of SAH, Am80 promoted M1-to-M2 phenotypic polarization in microglia and suppressed the nuclear transcription of NF-κB. Conclusion: Activation of the RARα receptor attenuated neuroinflammation by promoting M1-to-M2 phenotypic polarization in microglia and regulating the Mafb/Msr1/PI3K-Akt/NF-κB pathway. RARα might serve as a potential target for SAH therapy.